Women’s Awareness of Sexual Harassment Policies in Higher Education Institutions in Pakistan: A Study on Perceptions, Barriers, and Impacts - Khalida khan; Prof Dr. Arabella Bhutto; Prof Dr. Asif Ali Shah (Dialogue Social Science Review (DSSR), 2025)
Analyzing harassment and discrimination against female faculty members at higher education institutions was the study's main goal. The study's primary goals were to identify the primary causes of harassment and discrimination in higher education institutions as well as to highlight the types and contributing variables of harassment that often occur there. The study was descriptive in nature, and data was collected from a subset of Sindh's higher education institutions using a quantitative research technique. A random sample of 160 female faculty members from various universities participated in the quantitative portion of the study. Data study led to the conclusion that harassment at higher education institutions is becoming more common. Women's knowledge of the workplace's sexual harassment policy as opposed to formal statements made by the organizational hierarchy According to recent theory and research, employees' attitudes and behaviors regarding gender discrimination and harassment are frequently and significantly influenced by their perceptions of the organizational ease of sexual harassment, their opinions about the situation at work, or their worries about practical justice rather than the merely objective existence of formal rules and regulations. This study investigates the degree of knowledge regarding harassment and discrimination policies as well as the types of harassment that most frequently occur at work. The most common issues are those that affect women's health, social contacts, communication with authorities, and personal reputations. The vast majority of participants concern that physical, psychological, and emotional abuse of women is commonplace in higher education settings. This study also examines how the majority of women typically experienced physical and verbal abuse from males at work, as well as violence against social issues.